Technical procedure of endovenous laser ablation for chronic venous insufficiency - Suprayoga, Imam Mi'raj; Kurnianingsih, Novi (Universitas Brawijaya, 2025)
Venous insufficiency is an often-encountered medical issue. In recent years, a number of procedures have been developed for the treatment of venous insufficiency within the context of minimally invasive surgery. Endovenous laser ablation (EVLA) is a commonly used contemporary method. The ultimate outcome is the formation of fibrotic tissue that seals the lumen of the treated vein. Vein ablation procedures are often performed with local-tumescent anaesthesia, allowing patients to be treated in an office environment and resume full activity immediately afterwards. The use of EVLA is strongly recommended above surgical intervention or foam sclerotherapy, as indicated by a 1A class recommendation. The approach seems to possess significant attributes and benefits in terms of safety and efficacy. This article provides an overview of the technical technique involved in EVLA for the treatment of venous insufficiency. Additionally, it emphasises the significance of EVLA in managing venous insufficiency.